Association among Polymorphisms in EGFR Gene Exons, Lifestyle and Risk of Gastric Cancer with Gender Differences in Chinese Han Subjects - Zhang, Junfeng; Zhan, Zhen; Wu, Juan; Zhang, Chunbing; Yang, Yaping; Tong, Shujuan; Sun, Zheng; Qin, Lei; Yang, Xuewen; Dong, Wei (PloS one, 2013)
The epidermal growth factor receptor (EGFR) gene plays a key role in tumor survival, invasion, angiogenesis, and metastatic spread. Recent studies showed that gastric cancer (GC) was associated with polymorphisms of the EGFR gene and environmental influences, such as lifestyle factors. In this study, seven known SNPs in EGFR exons were investigated in a high-risk Chinese population in Jiangsu province to test whether genetic variants of EGFR exons and lifestyle are associated with an increased risk of GC. A hospital-based case-control study was performed in Jiangsu province. The results showed that smoking, drinking and preference for salty food were significantly associated with the risk of GC. The differences of lifestyle between males and females might be as the reason of higher incidence rates in males than those in females. Seven exon SNPs were genotyped rs2227983,rs2072454,rs17337023,rs1050171,rs1140475, rs2293347, and rs28384375. It was noted that the variant rs2072454 T allele and TT genotype were significantly associated with an increased risk of GC. Interestingly, our result suggested the ACAGCA haplotype might be associated with decreased risk of GC. However, no significant association was examined between the other six SNPs and the risk of GC both in the total population and the age-matching population even with gender differences. Smoking, drinking and preference for salty food were significantly associated with the risk of GC in Jiangsu province with gender differences. Although only one SNP (rs2072454) was significantly associated with an increased risk of GC, combined the six EGFR exon SNPs together may be useful for predicting the risk of GC.